FDG-Avid Lung Nodule Formation by the Use of Hemostatic Powder: A Potential Cause of False-Positive FDG PET/CT - (:unkn) unknown (Lippincott Williams and Wilkins, 2021)
FDG PET/CT is used in the diagnosis and follow-up of various malignant tumors and changes patient management in routine clinical practice. However, inflammatory, infectious, physiological, and technical causes and benign pathological conditions may lead to false-positive FDG uptake. We report a case of a 59-year-old man who was considered having a false-positive FDG-PET pulmonary nodular lesion in favor of metastasis, which was formed by the use of hemostatic powder. © Wolters Kluwer Health, Inc. All rights reserved.
Keywords: FDG PET/CT; hemostatic agent; pulmonary nodule